Educação natural e infância segundo Jean Jacques Rousseau - Tomazelli, Gilberto Luiz (2008)
This is a bibliographical investigation about the two first books of Emílio ou da educação writing for Emilio Jean Jacques Rousseau with the support of the secondary literature that deals of the subject. It has for purpose to offer, in the first chapter, some information on the historical context in which if it inserts the thought of Rousseau, taking as reference the concepts of enlightenment, infancy and education. The second chapter presents a panoramic vision of two first books of Emilio to prepare the discussion on the inquiry problem. The third and last chapter of the work analyzes the tension that if establishes between the necessities of the child and the cares of the adult. The project of natural education and the concept of infancy are deeply tied with the rousseauniana comprehension of infantile necessity and the way as the adult must exert its cares to assist in the satisfaction of such necessities. The child does not have to be enslaved by the adult and at the same time not to enslave it. This denotes the fact of that Rousseau thinks the pedagogical relation between child and adult searching to escape two extreme positions, unstudied and the authoritarianism. In this context, it takes the education for the things as basic normative reference of the infantile education and attributes to the adult the paper to facilitate the contact of the child with the nature, conceived in the scope of the project of the natural education directed infancy, as the great teacher